The Film Adaptation of Atonement - An Analysis of the “Point of View” in Cinema and Literature and their Semiotic Implications - Alves, Soraya Ferreira (Estudos Semióticos, 2011)
This paper aims at discussing the ways words and image interact, as well as the dialogue between literature and cinema taking the novel “Atonement” by Ian McEwan (2001) and the ﬁlm adaptation by director Joe Wright (2007) as examples to be analyzed. The novel, a metaﬁctional one, narrates the story of two lovers whose destinies where marked by the misjudgement of another character that, as time goes by, tries to atone for her mistake. Wright’s ﬁlm keeps the same plot, but uses a diﬀerent resource by inverting the presentation of the points of view, resulting in a diﬀerent construction of the story by the viewer. This analysis will try to demonstrate how the ﬁlm adaptation of “Atonement” resigniﬁes the literary work, observing the peculiar literary and cinematographic resources regarding narration and point of view. It is based on the concept of rewriting as postulated by Lefevere which takes into consideration who rewrites, under what circumstances, and whom the rewriting is direct to. We also intend to discuss the diversity of interpretation grounded in semiotic theory by Charles Peirce, speciﬁcally concerning the point of view.